Rancang Bangun 3 Dimensi Hologram Sebagai Media Informasi Mengenal Hewan Mamalia - Dyandra Hutama Abdi; Rismayanti Rismayanti; Putri Harliana (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2022)
The development of digital technology today has grown rapidly in everyday life. Advances in technology can now be accessed easily so that users of computer technology encourage people to be creative and innovate. However, the development of the past few years, the world of visual communication design has begun to develop towards an alternative 3d virtual reality technology called "holography". Hologram is a technology that is able to record the scattered light from an object and present it in 3D. The animated image can then be presented in 360 degrees and can move with animation in order to convey information, either in real time or not. This hologram was created using 3DsMax 2018 software and edited animated videos with Adobe Premiere Pro cc 2020. Through the design and application of this hologram concept, the author finds out how to design a 3D hologram animation, by creating a system that will make it easier for people to see information and be able to visualize the shape of mammals more attractively and stay modern in accordance with the times. The final result of this hologram design is to be able to display holographic animation videos in the form of several characters of mammals that will be displayed through the acrylic pyramid media.Keywords: 3D Animation, 3DsMax, Adobe Premiere Pro 2020, Hologram